Effect of rice straw, biochar and calcite on maize plant and Ni bio-availability in acidic Ni contaminated soil. (1st April 2020) - Ali, Umeed; Shaaban, Muhammad; Bashir, Saqib; Fu, Qingling; Zhu, Jun; Shoffikul Islam, Md; Hu, Hongqing
Abstract: Metals that contaminate soil is one of the major problems seriously affecting sustainable agriculture worldwide. Nickel (Ni) toxicity to agricultural crops is a global problem. Mobility of heavy metals present in contaminated soil can be reduced by the amendment of soil passivators, which will ultimately reduce the risk of them entering the food chain. A greenhouse pot experiment was conducted to investigate the effects of rice straw (RS), biochar derived from rice straw (BI) and calcium carbonate (calcite) on Ni mobility and its up take by maize ( Zea maize L.) plant. Maize crop was grown in Ni spiked (100 mg kg −1 ) soil with three application rates of passivators (equivalent to 0, 1and 2% of each RS, BI and calcite) applied separately to the soil. Results revealed that the post-harvest soil properties (pH, DOC and MBC), plant phenology (plant height, root length, total dry weight) and physiological characteristics were significantly enhanced with passivator application. Additionally, incorporating passivator into the soil reduced Ni mobility (DTPA) by 68%, 88.9% and 79.3%, and leachability (TCLP) by 72.4%, 76.7% and 66.7% for RS, BI and calcite, respectively at 2% application rate. The Ni concentration in the maize shoots reduced by 30%, 95.2% and 95% and in the roots by 56%, 66% and 63.8% with RS, BI and calcite at 2% application rate, respectively. These findings suggest that the application of 2% biochar (BI) is very promising in reducing Ni uptake, and can reduce toxicity to plants, decrease mobility and leachability in the soil. Graphical abstract: Image 101194 Highlights: BI, calcite and RS were fabricated and applied for Ni remediation in acidic soil. BI was more effective for Ni passivation with 88% reduction of bioavailable. Ni Well dispersion and extra adsorption sites in BI facilitated Ni binding. BI can effectively increase alkalinization and thereby reduced the Ni phytotoxicity on maize.